Crystallochemical aspects of solid state reactions in mechanically alloyed Al-Cu-Fe quasicrystalline powders - Salimon, A; Korsunsky, A; Shelekhov, E; Sviridova, T; Kaloshkin, S; Tcherdyntsev, V; Baldokhin, Y (Pergamon, 2001)
A number of elemental mixtures have initial compositions close to Al₆₅Cu₂₃Fe₁₂ were mechanically alloyed at different energy intensities using a planetary mill. Laboratory X-ray diffraction analysis, differential scanning calorimetry and Mössbauer spectroscopy were used for characterization of the phase and structural state of mechanically alloyed powders after different periods of milling and annealing. Several exothermic effects were found, and these were ascribed to specific solid-state reactions. Quantitative phase analysis was applied in order to identify the mechanism of solid-state reactions taking place in the vicinity of the quasicrystalline phase domain in the Al-Cu-Fe system as a result of mechanical and thermal excitation and homogenization. Metastable intermetallics were identified which possess certain structural and topological elements identical to those found in quasicrystals.